Ligand-coated doped lithium iron phosphate and preparation method and application thereof

By introducing doping and coating technology of composite loaded microcarbon spherical conductors and liquid ligands into lithium iron phosphate, the Mn-T-C/N frame structure is formed, which solves the high cost and low thermal stability of the lithium battery positive electrode material. and the problem of poor circulation performance, higher discharge specific capacity and improved circulation performance are achieved.

CN114373911BActive Publication Date: 2025-02-07GUANGDONG BRUNP RECYCLING TECH CO LTD +2

Patent Information

Application Number
CN202111634305.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-02-07
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

Existing lithium battery positive electrode materials such as lithium cobalt oxide and lithium manganese oxide have problems such as high cost, low thermal stability, poor circulation performance, and the charging and discharging efficiency of lithium iron phosphate is not satisfactory.

Method used

Using ligand-coated doped lithium iron phosphate (LiFePO4@Mn-T-C/N), the doping and coating of lithium iron phosphate with a composite loaded microcarbon spherical conductor and liquid-phase ligand is used to form Mn- T-C/N frame structure to improve the structural stability and electrochemical properties of the material.

Benefits of technology

The structural stability and electrochemical performance of lithium iron phosphate have been significantly improved, the discharge specific capacity is higher, the cycle performance is improved, and the preparation method is low-cost and simple, which is conducive to commercial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114373911B_ABST
    Figure CN114373911B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium ion batteries, and discloses a ligand-coated doped lithium iron phosphate and a preparation method and application thereof. The general formula of the ligand-coated doped lithium iron phosphate is LiFePO4@Mn-T-C / N; T is at least one of zinc, nickel, copper, iron, cobalt, zirconium, aluminum, gallium, and chromium. The doped type in the ligand-coated doped lithium iron phosphate of the present invention is doped by a composite-loaded micro-carbon sphere conductor, and the particle size of the composite-loaded micro-carbon sphere conductor reaches 80-150nm level, so it can withstand greater stress and reduce the probability of rupture. The spherical lithium iron phosphate doped with the composite-loaded micro-carbon sphere conductor has a more easily controlled material structure integrity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to ligand-coated doped lithium iron phosphate and a preparation method and application thereof. Background Art

[0002] At present, relatively mature lithium battery positive electrode materials mainly contain transition metal oxides (lithium cobalt) oxides, lithium manganese oxide, olivine-type structure, etc.), fluorine and chlorine compounds. Lithium cobalt oxide positive electrode materials are the most successful business model and were originally commercialized by Sony. But its main limitations are high cost and low thermal stability, which can easily cause spontaneous combustion, such as the spontaneous combustion and explosion of a certain brand of mobile phones and electric vehicles. Lithium manganese oxide has relatively low toxicity and low price, but its cycle performance is particularly low, which also limits the further commercialization of lithium manganese oxide. Due to the higher theoretical specific capacity and capacity, metal chlorides and fluorides have been widely studied. However, metal chlorides and fluorides usually have problems such as poor conductivity, volume expansion, and unnecessary side reactions.

[0003] Lithium iron phosphate (LFP), this material has an olivine structure, is cheap, extremely stable, non-toxic and environmentally friendly, and is particularly suitable for use in power lithium batteries. However, its charge and discharge efficiency is not satisfactory. In view of its excellent performance, it is worth studying to modify and improve the charge and discharge rate of lithium iron phosphate. Generally speaking, a single modification test is often limited by conditions, and the modification effect is not good, especially for lithium iron phosphate positive electrode materials. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a ligand-coated doped lithium iron phosphate and a preparation method and application thereof, wherein the ligand-coated doped lithium iron phosphate has excellent structural stability and electrochemical performance.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A ligand-coated doped lithium iron phosphate has a general formula of LiFePO4@Mn-TC / N, wherein T is at least one of zinc, nickel, copper, iron, cobalt, zirconium, aluminum, gallium, and chromium.

[0007] Preferably, T is at least one of zinc, nickel, copper, cobalt, zirconium and gallium.

[0008] Preferably, the Mn-TC / N is Mn-T loaded on C / N. The C / N is a micro carbon sphere conductor.

[0009] Preferably, the ligand-coated doped lithium iron phosphate is one of LiFePO4@Mn-Zn / Ga-C / N, LiFePO4@Mn-Cu / Co / Zr-C / N, LiFePO4@Mn-Zn / Co-C / N, LiFePO4@Mn-Co / Cu-C / N, LiFePO4@Mn-Zr / Cu-C / N, LiFePO4@Mn-Zr / Cu-C / N, LiFePO4@Mn-Zr / Cu / Co-C / N, and LiFePO4@Mn-Zn / Cu / Co-C / N.

[0010] A method for preparing ligand-coated doped lithium iron phosphate, the method being used for preparing the above-mentioned coated lithium iron phosphate.

[0011] Specifically, a method for preparing ligand-coated doped lithium iron phosphate comprises the following steps:

[0012] The phosphate fertilizer, the iron source and the regulator are mixed, heated for reaction, solid-liquid separation, and the solid phase is taken for the first calcination to obtain iron phosphate;

[0013] The iron phosphate, lithium source, carbon source and micro-carbon ball conductor are mixed and stirred, and calcined for a second time to obtain micro-carbon ball conductor doped lithium iron phosphate;

[0014] The micro-carbon ball conductor is doped with lithium iron phosphate, sulfite, and liquid ligand, mixed and stirred, aged, cross-linked, and calcined for the third time to obtain the ligand-coated doped lithium iron phosphate; the micro-carbon ball conductor includes nano-carbon balls, 1,6-bis(dimethylamino)hexane, a manganese source, a T source, methacrylamide, and a dispersant; the T source includes at least one of soluble chlorides, nitrates, and sulfates of zinc, nickel, copper, iron, cobalt, zirconium, aluminum, gallium, and chromium.

[0015] Preferably, the molar ratio of P in the phosphate fertilizer, Fe in the iron source, Li in the lithium source, and C in the carbon source is 1: (0.95-1.10): (0.95-1.15): (0.05-0.30).

[0016] Preferably, the phosphate fertilizer is at least one of diammonium phosphate, diammonium hydrogen phosphate, ammonium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate or potassium phosphite.

[0017] Further preferably, the phosphate fertilizer has a purity reaching battery grade.

[0018] More preferably, the phosphate fertilizer contains Ca≤50ppm, Mg≤50ppm, zinc≤50ppm, potassium≤100ppm, sodium≤100ppm, F≤10ppm, S≤30ppm, and Cl≤30ppm.

[0019] Preferably, the iron source is at least one of ferric chloride, ferric acetate, ferric nitrate, ferric sulfate, ferric hydroxide or ferric oxalate.

[0020] Preferably, the heating reaction further comprises controlling the pH of the reaction system to ≤3.0.

[0021] Preferably, the regulating agent is at least one of octadecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide or dodecyltrimethylammonium bromide.

[0022] Preferably, the amount of the regulator added is 0.001-0.010 of the total mass of the phosphate fertilizer and the iron source.

[0023] Preferably, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium chloride, lithium formate, lithium phosphate, lithium oxalate, lithium sulfate, lithium nitrate or lithium bromide.

[0024] Preferably, the carbon source is at least one of maltose powder, corn syrup, honey, glucose powder or starch.

[0025] Preferably, the atmosphere of the first calcination is one of N2, Ne, Ar or Kr.

[0026] Preferably, the temperature of the first calcination is 380-950° C., and the time of the first calcination is 4-20 h.

[0027] Preferably, the amount of the micro-carbon ball conductor added is 0.001-0.05 of the total mass of the iron phosphate and the lithium source.

[0028] Preferably, the preparation method of the micro-carbon sphere conductor comprises the following specific steps: (1) uniformly mixing, stirring, centrifuging, filtering and drying nano-carbon spheres, a manganese source, a T source, methacrylamide and a dispersant to obtain a composite-loaded micro-carbon sphere conductor precursor; (2) uniformly mixing the composite-loaded micro-carbon sphere conductor precursor, 1,6-bis(dimethylamino)hexane and a dispersant, and heat treating to obtain a micro-carbon sphere conductor.

[0029] Further preferably, the nano-carbon spheres, manganese source, T source, methacrylamide and dispersant are mixed in a solid-liquid ratio of (0.5-5) g: (0.1-1) g: (0.1-1) g: (1-5) ml: (5-20) ml.

[0030] More preferably, the heat treatment is carried out at a temperature of 300-800° C. and for a time of 30-120 min.

[0031] Preferably, the manganese source is at least one of manganese chloride, manganese nitrate and manganese sulfate.

[0032] Preferably, the dispersant is at least one of methanol, ethanol, ethylene glycol, glycerol, polyvinyl alcohol, polyethylene glycol, n-butanol, isobutanol, and water.

[0033] Preferably, the aging temperature is 95-150° C., and the aging time is 4-12 h.

[0034] Preferably, the atmosphere of the second calcination is one of N2, Ne, Ar or Kr.

[0035] Preferably, the temperature of the second calcination is 380-950° C., and the time of the second calcination is 4-20 hours.

[0036] Preferably, the sulfite is at least one of ferrous sulfite, sodium sulfite, potassium sulfite, lithium sulfite and ammonium sulfite.

[0037] Preferably, the amount of sulfite added is 0.001-0.1 of the mass of lithium iron phosphate, and further preferably, the amount of sulfite added is 0.003-0.01 of the mass of lithium iron phosphate.

[0038] Preferably, the liquid phase ligand is prepared by mixing the ligand and the dispersant at a solid-liquid ratio of (0.1-0.5):(2-10) g / ml.

[0039] Further preferably, the added amount of the ligand is 0.0001-0.03 of the mass of lithium iron phosphate.

[0040] More preferably, the added amount of the ligand is 0.005-0.01 of the mass of lithium iron phosphate.

[0041] Further preferably, the ligand is at least one of 1,6-bis(1H-imidazole-4-carboxylic acid)hexyl, 1,2-bis(1H-imidazole-4-carboxamide)ethyl, 4-hydroxy-(1,1'-biphenyl)-3,5-dicarboxylic acid dimethyl ester, and 1,1',1"-(nitrotri(benzene-4,1-diacyl))triethyl ketone.

[0042] Preferably, the atmosphere of the third calcination is one of N2, Ne, Ar or Kr.

[0043] Preferably, the temperature of the third calcination is 380-950° C., and the time of the third calcination is 4-18 hours.

[0044] The present invention also provides a battery, comprising the ligand-coated doped lithium iron phosphate.

[0045] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0046] 1. The doped lithium iron phosphate coated with ligands of the present invention is doped with a composite loaded micro-carbon sphere conductor. The particle size of the composite loaded micro-carbon sphere conductor reaches 80-150nm, so it can withstand greater stress and reduce the probability of rupture. The spherical lithium iron phosphate doped with the composite loaded micro-carbon sphere conductor is easier to control the integrity of the material structure; in addition, it can contribute a considerable specific surface area. The synergistic effect of the various metal ions loaded by the micro-carbon sphere conductor can shorten the migration path of electrons inside the material and improve the conductivity of the material. Therefore, the composite loaded micro-carbon sphere conductor doping can stabilize the stability of the overall structure of the spherical lithium iron phosphate material and improve the electrochemical performance. Through 50 discharge cycles, compared with the preparation of comparative examples 1-3, the lithium iron phosphate prepared in Example 1-6 has a higher discharge specific capacity and a better structure, and the cycle performance of the spherical lithium iron phosphate positive electrode material is correspondingly improved. The ligand coating in the ligand-coated doped lithium iron phosphate, the Mn-TC / N framework structure formed by part of the liquid phase ligand and Mn and T will strengthen the spherical lithium iron phosphate.

[0047] 2. In the preparation method of the present invention, lithium iron phosphate, sulfite, and liquid-phase ligand are mixed, stirred, aged, cross-linked, and calcined for the third time. On the one hand, by adding sulfite, the iron in the spherical lithium iron phosphate is prevented from being oxidized, which is beneficial to the ex situ liquid-phase ligand coating. On the other hand, after the spherical lithium iron phosphate is aged in the liquid-phase ligand, it can be cross-linked with the metal loaded by the doped composite-loaded micro-carbon sphere conductor, and the spherical lithium iron phosphate-doped micro-carbon sphere conductor loads metals Mn and T, and part of the liquid-phase ligand will form a Mn-TC / N framework structure with Mn and T, and the Mn-TC / N framework structure will strengthen the spherical lithium iron phosphate; the coating strategy of the ligand liquid-phase coating of the spherical lithium iron phosphate positive electrode material provides a new idea for the modification of positive electrode materials.

[0048] 3. The composite loaded micro-carbon sphere conductor of the present invention not only has high conductivity and high chemical stability, but also has low manufacturing cost and simple synthesis. Therefore, it has a positive impact on the improvement of spherical lithium iron phosphate positive electrode materials and is conducive to the further commercial application of lithium iron phosphate positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a SEM image of the micro-carbon sphere conductor prepared in Example 4 of the present invention;

[0050] Figure 2 TEM image of the micro carbon sphere conductor prepared in Example 4 of the present invention;

[0051] Figure 3 This is a SEM image of the ligand-coated doped lithium iron phosphate prepared in Example 4 of the present invention;

[0052] Figure 4This is a graph of the 1st to 50th discharge specific capacities of the ligand-coated doped lithium iron phosphate prepared in Example 4 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0053] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0054] Example 1

[0055] The ligand-coated doped lithium iron phosphate of this embodiment has a chemical formula of LiFePO4@Mn-Zn / Ga-C / N.

[0056] The preparation method of the ligand-coated doped lithium iron phosphate of this embodiment comprises the following specific steps:

[0057] (1) 100 mL of 0.74 mol / L ammonium dihydrogen phosphate and 70 mL of 0.50 mol / L ferric sulfate were added dropwise to a 500 mL reactor and stirred. During the process, 20 mL of 0.20 g of octadecyltrimethylammonium chloride solution was added dropwise, and an appropriate amount of phosphoric acid was added to control the pH of the solution to 2.3. The reactor was sent to a heating box and heated at 585° C. for 6 h under Ar. The reactor was allowed to stand overnight, filtered, washed, and dried to obtain 11.7 g of spherical ferric phosphate;

[0058] (2) 2.5 g of nanocarbon spheres, 0.05 g of manganese sulfate, 0.05 g of zinc chloride, 0.05 g of gallium sulfate, 1.2 g of methacryloyl, and 5 mL of deionized water were uniformly mixed, stirred, centrifuged, and filtered, and then dried in a drying oven at 150° C. for 5 h to obtain 3.3 g of manganese-zinc-gallium composite-loaded microcarbon sphere conductor precursor;

[0059] (3) 3.3 g of manganese-zinc-gallium composite supported micro-carbon sphere conductor precursor, 0.5 g of 1,6-bis(dimethylamino)hexane, and 7 mL of ethanol were uniformly mixed, sent to a heating box filled with Ar, and treated at 420° C. for 35 min to obtain 3.7 g of micro-carbon sphere conductor;

[0060] (4) 11.7 g of spherical iron phosphate, 0.1 g of micro-carbon ball conductor, 1.8 g of lithium hydroxide, 0.3 g of corn syrup, and 20 mL of polyethylene glycol were mixed and stirred, and then sent to a heating box for drying, and heated at 650° C. for 8 h under Ar to obtain 12.3 g of micro-carbon ball conductor doped spherical lithium iron phosphate;

[0061] (5) 0.15 g of ammonium sulfite, 12.3 g of micro-carbon ball conductor doped spherical lithium iron phosphate, and 15 mL of polyethylene glycol (containing 0.35 g of 1,6-bis(1H-imidazole-4-carboxylic acid)hexyl) were added to a reaction kettle and stirred, aged at 95 °C for 10 h, heated at 450 °C for 7.5 h in an Ar atmosphere, crushed, washed, dried, and demagnetized to obtain ligand-coated micro-carbon ball conductor doped lithium iron phosphate LiFePO4@Mn-Zn / Ga-C / N.

[0062] Example 2

[0063] The ligand-coated doped lithium iron phosphate of this embodiment has a chemical formula of LiFePO4@Mn-Zn / Co-C / N.

[0064] The preparation method of the ligand-coated doped lithium iron phosphate of this embodiment comprises the following specific steps:

[0065] (1) 110 mL of 0.74 mol / L ammonium dihydrogen phosphate and 73 mL of 0.50 mol / L ferric sulfate were added dropwise to a 500 mL high temperature resistant reaction kettle and stirred. During the stirring, 20 mL of 0.20 g of octadecyltrimethylammonium chloride solution was added dropwise. An appropriate amount of phosphoric acid was added to control the pH value of the solution to 2.3. The reaction kettle was sent to a heating box and heated at 585° C. for 6 h under Ar. The reaction kettle was allowed to stand overnight, filtered, washed, and dried to obtain 11.7 g of spherical ferric phosphate.

[0066] (2) 2.5 g of nanocarbon spheres, 0.05 g of manganese sulfate, 0.05 g of zinc chloride, 0.05 g of cobalt sulfate, 1.0 g of methacryloyl, and 5 mL of deionized water were uniformly mixed, stirred, centrifuged, and filtered, and then dried in a drying oven at 150° C. for 5 h to obtain 3.3 g of manganese-zinc-cobalt composite-loaded microcarbon sphere conductor precursor;

[0067] (3) 3.3 g of manganese-zinc-cobalt composite supported micro-carbon sphere conductor precursor, 0.5 g of 1,6-bis(dimethylamino)hexane, and 7 mL of ethanol were uniformly mixed, sent to a heating box filled with Ar, and treated at 420° C. for 35 min to obtain 3.7 g of micro-carbon sphere conductor;

[0068] (4) 11.7 g of spherical iron phosphate, 0.15 g of micro-carbon ball conductor, 1.8 g of lithium hydroxide, 0.3 g of corn syrup, and 20 mL of polyethylene glycol were mixed and stirred, and then sent to a heating box for drying, and heated at 650° C. for 8 h under Ar to obtain 12.4 g of micro-carbon ball conductor doped spherical lithium iron phosphate;

[0069] (5) 0.18 g of ammonium sulfite, 12.4 g of micro-carbon ball conductor doped spherical lithium iron phosphate, and 18 mL of polyethylene glycol (containing 0.4 g of 1,6-bis(1H-imidazole-4-carboxylic acid)hexyl) were added into a reaction kettle and stirred, aged at 95 °C for 10 h, heated at 540 °C for 6 h in an Ar atmosphere, crushed, washed, dried, and demagnetized to obtain ligand-coated micro-carbon ball conductor doped lithium iron phosphate LiFePO4@Mn-Zn / Co-C / N.

[0070] Example 3

[0071] The ligand-coated doped lithium iron phosphate of this embodiment has a chemical formula of LiFePO4@Mn-Co / Cu-C / N.

[0072] The preparation method of the ligand-coated doped lithium iron phosphate of this embodiment comprises the following specific steps:

[0073] (1) 115 mL of 0.74 mol / L ammonium dihydrogen phosphate and 75 mL of 0.50 mol / L ferric sulfate were added dropwise to a 500 mL high temperature resistant reaction kettle and stirred. During the stirring, 25 mL of 0.20 g of octadecyltrimethylammonium chloride solution was added dropwise. An appropriate amount of phosphoric acid was added to control the pH value of the solution to 2.4. The reaction kettle was sent to a heating box and heated at 585° C. for 6 h under Ar. The reaction kettle was allowed to stand overnight, filtered, washed, and dried to obtain 11.9 g of spherical ferric phosphate;

[0074] (2) 2.5 g of nanocarbon spheres, 0.06 g of manganese sulfate, 0.06 g of zinc chloride, 0.04 g of gallium sulfate, 1.5 g of methacryloyl, and 9 mL of deionized water were uniformly mixed, stirred, centrifuged, and filtered, and then dried in a drying oven at 150° C. for 5 h to obtain 3.5 g of manganese-cobalt-copper composite-loaded microcarbon sphere conductor precursor;

[0075] (3) 3.5 g of manganese-cobalt-copper composite supported micro-carbon sphere conductor precursor, 0.65 g of 1,6-bis(dimethylamino)hexane, and 7 mL of ethanol were uniformly mixed, sent to a heating box filled with Ar, and treated at 420° C. for 35 min to obtain 3.9 g of micro-carbon sphere conductor;

[0076] (4) 11.9 g of spherical iron phosphate, 0.2 g of micro-carbon ball conductor, 1.9 g of lithium hydroxide, 0.3 g of corn syrup, and 22 mL of polyethylene glycol were mixed and stirred, and then sent to a heating box for drying, and heated at 650° C. for 8 h under Ar to obtain 12.3 g of micro-carbon ball conductor doped spherical lithium iron phosphate;

[0077] (5) 0.2 g of ammonium sulfite, 12.3 g of micro-carbon ball conductor doped spherical lithium iron phosphate, and 20 mL of polyethylene glycol (containing 0.5 g of 1,2-bis(1H-imidazole-4-carboxamide)ethyl) were added to a reaction kettle and stirred, aged at 120°C for 9 h, heated at 590°C for 5 h in an Ar atmosphere, crushed, washed, dried, and demagnetized to obtain ligand-coated micro-carbon ball conductor doped lithium iron phosphate LiFePO4@Mn-Co / Cu-C / N.

[0078] Example 4

[0079] The ligand-coated doped lithium iron phosphate of this embodiment has a chemical formula of LiFePO4@Mn-Zr / Cu-C / N.

[0080] The preparation method of the ligand-coated doped lithium iron phosphate of this embodiment comprises the following specific steps:

[0081] (1) 110 mL of 0.74 mol / L potassium dihydrogen phosphate and 70 mL of 0.53 mol / L ferric nitrate were added dropwise to a 500 mL high temperature resistant reaction kettle and stirred. During the stirring, 20 mL of 0.20 g of hexadecyltrimethylammonium bromide solution was added dropwise. An appropriate amount of phosphoric acid was added to control the pH value of the solution to 2.6. The reaction kettle was sent to a heating box and heated at 585° C. for 6 h under Ar. The reaction kettle was allowed to stand overnight, filtered, washed, and dried to obtain 11.8 g of spherical iron phosphate;

[0082] (2) 2.5 g of nanocarbon spheres, 0.10 g of manganese sulfate, 0.05 g of zirconium sulfate, 0.08 g of copper chloride, 1.0 g of methacryloyl, and 6 mL of deionized water were uniformly mixed, stirred, centrifuged, and filtered, and then dried in a drying oven at 150° C. for 5 h to obtain 2.9 g of manganese-zirconium-copper composite-loaded microcarbon sphere conductor precursor;

[0083] (3) 2.9 g of manganese zirconium copper composite supported micro carbon sphere conductor precursor, 0.5 g of 1,6-bis(dimethylamino)hexane, and 7 mL of ethanol were uniformly mixed, sent to a heating box filled with Ar, and treated at 460° C. for 42 min to obtain 3.3 g of micro carbon sphere conductor;

[0084] (4) 11.8 g of spherical iron phosphate, 1.85 g of lithium hydroxide, 0.3 g of glucose, 0.2 g of micro carbon sphere conductor, and 20 mL of polyethylene glycol were mixed and stirred, and then sent to a heating box for drying, and heated at 650° C. for 8 h under Ar to obtain 12.3 g of micro carbon sphere conductor doped spherical lithium iron phosphate;

[0085] (5) 0.12 g of lithium sulfite, 12.3 g of micro-carbon ball conductor doped spherical lithium iron phosphate, and 12 mL of polyethylene glycol (containing 0.3 g of 4-hydroxy-(1,1'-biphenyl)-3,5-dicarboxylic acid dimethyl ester) were added into a reaction kettle and stirred, aged at 130 ° C for 7 h, heated at 650 ° C for 4 h under Ar, crushed, washed, dried, and demagnetized to obtain ligand-coated micro-carbon ball conductor doped lithium iron phosphate LiFePO4@Mn-Zr / Cu-C / N.

[0086] Figure 1 This is a SEM image of the micro-carbon sphere conductor of Example 4 of the present invention; Figure 2 TEM image of the micro carbon sphere conductor of Example 4 of the present invention; Figure 1 , 2 The size of the micro-carbon sphere conductor is between 100-200nm, most of them are spherical, the particles are relatively uniform, and a small part is broken and incomplete.

[0087] Figure 3 This is a SEM image of the ligand-coated doped lithium iron phosphate of Example 4 of the present invention; Figure 3 The particle shape of the doped lithium iron phosphate after the ligand coating is not obvious, and many lithium iron phosphate particles are bonded together, with a size of 100-300nm, and the particle diameter increases.

[0088] Example 5

[0089] The ligand-coated doped lithium iron phosphate of this embodiment has a chemical formula of LiFePO4@Mn-Zr / Cu / Co-C / N.

[0090] The preparation method of the ligand-coated doped lithium iron phosphate of this embodiment comprises the following specific steps:

[0091] (1) 100 mL of 0.74 mol / L potassium dihydrogen phosphate and 76 mL of 0.53 mol / L ferric nitrate were added dropwise to a 500 mL high temperature resistant reaction kettle and stirred. During the stirring, 20 mL of a solution containing 0.20 g of hexadecyltrimethylammonium bromide was added dropwise. An appropriate amount of phosphoric acid was added to control the pH value of the solution to 2.3. The reaction kettle was sent to a heating box and heated at 585° C. for 6 h under Ar. The reaction kettle was allowed to stand overnight, filtered, washed, and dried to obtain 11.7 g of spherical iron phosphate;

[0092] (2) 4.0 g of nanocarbon spheres, 0.12 g of manganese sulfate, 0.07 g of zirconium sulfate, 0.12 g of copper chloride, 0.04 g of cobalt sulfate, 1.2 g of methacryloyl, and 12 mL of deionized water were uniformly mixed, stirred, centrifuged, and filtered, and then dried in a drying oven at 150° C. for 5 h to obtain 4.4 g of manganese-zirconium-copper-cobalt composite-supported microcarbon sphere conductor precursor;

[0093] (3) 3.4 g of manganese zirconium copper cobalt composite supported micro carbon sphere conductor precursor, 0.6 g of 1,6-bis(dimethylamino)hexane, and 7 mL of ethanol were uniformly mixed, sent to a heating box filled with Ar, and treated at 460° C. for 42 min to obtain 3.6 g of micro carbon sphere conductor;

[0094] (4) 11.7 g of spherical iron phosphate, 1.8 g of lithium hydroxide, 0.35 g of glucose, 0.25 g of micro carbon sphere conductor, and 20 mL of polyethylene glycol were mixed and stirred, and then sent to a heating box for drying, and heated at 650° C. for 8 h under Ar to obtain 12.8 g of micro carbon sphere conductor doped spherical lithium iron phosphate;

[0095] (5) 0.15 g of lithium sulfite, 12.8 g of micro-carbon ball conductor doped spherical lithium iron phosphate, and 18 mL of polyethylene glycol (containing 0.35 g of 4-hydroxy-(1,1'-biphenyl)-3,5-dicarboxylic acid dimethyl ester) were added into a reaction kettle and stirred, aged at 140 ° C for 6 h, heated at 750 ° C for 3.5 h under Ar, crushed, washed, dried, and demagnetized to obtain ligand-coated micro-carbon ball conductor doped lithium iron phosphate LiFePO4@Mn-Zr / Cu / Co-C / N.

[0096] Example 6

[0097] The ligand-coated doped lithium iron phosphate of this embodiment has a chemical formula of LiFePO4@Mn-Zn / Cu / Co-C / N.

[0098] The preparation method of the ligand-coated doped lithium iron phosphate of this embodiment comprises the following specific steps:

[0099] (1) 120 mL of 0.74 mol / L potassium dihydrogen phosphate and 73 mL of 0.53 mol / L ferric nitrate were added dropwise to a 500 mL high temperature resistant reaction kettle and stirred. During the stirring, 20 mL of 0.20 g of hexadecyltrimethylammonium bromide solution was added dropwise. An appropriate amount of phosphoric acid was added to control the pH value of the solution to 2.3. The reaction kettle was sent to a heating box and heated at 585° C. for 6 h under Ar. The reaction kettle was allowed to stand overnight, filtered, washed, and dried to obtain 11.7 g of spherical iron phosphate;

[0100] (2) 4.2 g of nanocarbon spheres, 0.10 g of manganese sulfate, 0.05 g of zinc sulfate, 0.10 g of copper chloride, 0.08 g of cobalt sulfate, 1.5 g of methacryloyl, and 15 mL of deionized water were uniformly mixed, stirred, centrifuged, and filtered, and then dried in a drying oven at 150° C. for 5 h to obtain 4.6 g of manganese-zinc-copper-cobalt composite-supported microcarbon sphere conductor precursor;

[0101] (3) 2.9 g of manganese-zinc-copper-cobalt composite supported micro-carbon sphere conductor precursor, 0.5 g of 1,6-bis(dimethylamino)hexane, and 7 mL of ethanol were uniformly mixed, sent to a heating box filled with Ar, and treated at 460° C. for 42 min to obtain 3.3 g of micro-carbon sphere conductor;

[0102] (4) 11.7 g of spherical iron phosphate, 1.8 g of lithium hydroxide, 0.3 g of glucose, 0.2 g of micro carbon sphere conductor, and 20 mL of polyethylene glycol were mixed and stirred, and then sent to a heating box for drying, and heated at 650° C. for 8 h under Ar to obtain 12.3 g of micro carbon sphere conductor doped spherical lithium iron phosphate;

[0103] (5) 0.18 g of lithium sulfite, 12.1 g of micro-carbon ball conductor doped spherical lithium iron phosphate, and 20 mL of polyethylene glycol (containing 0.45 g of 4-hydroxy-(1,1'-biphenyl)-3,5-dicarboxylic acid dimethyl ester) were added into a reaction kettle and stirred, aged at 150 ° C for 4 h, heated at 950 ° C for 3 h under Ar, crushed, washed, dried, and demagnetized to obtain ligand-coated micro-carbon ball conductor doped lithium iron phosphate LiFePO4@Mn-Zn / Cu / Co-C / N.

[0104] Comparative Example 1 (Undoped Micro-Carbon Ball Conductor)

[0105] The ligand-coated lithium iron phosphate of this comparative example has a chemical formula of LiFePO4@-C / N.

[0106] The preparation method of the ligand-coated lithium iron phosphate of this comparative example comprises the following specific steps:

[0107] (1) 100 mL of 0.74 mol / L ammonium dihydrogen phosphate and 73 mL of 0.50 mol / L ferric sulfate were added dropwise to a 500 mL reactor and stirred. During the process, 20 mL of 0.20 g of octadecyltrimethylammonium chloride solution was added dropwise, and an appropriate amount of phosphoric acid was added to control the pH of the solution to 2.3. The reactor was sent to a heating box and heated at 585° C. for 6 h under Ar. The reactor was allowed to stand overnight, filtered, washed, and dried to obtain 11.7 g of spherical ferric phosphate;

[0108] (2) 11.7 g of spherical iron phosphate, 1.8 g of lithium hydroxide, 0.5 g of corn syrup, and 20 mL of polyethylene glycol were mixed and stirred, and then placed in a heating box for drying and heated at 650° C. for 8 h under Ar to obtain 12.3 g of spherical lithium iron phosphate;

[0109] (3) 0.15 g of ammonium sulfite, 12.3 g of spherical lithium iron phosphate, and 20 mL of polyethylene glycol (containing 0.5 g of 1,6-bis(1H-imidazole-4-carboxylic acid)hexyl) were added to a reaction kettle and stirred, aged at 120°C for 8 h, then heated at 450°C for 4.5 h under Ar filling, crushed, washed, dried, and demagnetized to obtain ligand-coated lithium iron phosphate LiFePO4@-C / N.

[0110] Comparative Example 2 (Uncoated with Ligand)

[0111] The doped lithium iron phosphate in this comparative example has a chemical formula of LiFePO4@Mn-Zn / Ga.

[0112] The preparation method of the doped lithium iron phosphate of this comparative example comprises the following specific steps:

[0113] (1) 100 mL of 0.74 mol / L potassium dihydrogen phosphate and 76 mL of 0.53 mol / L ferric nitrate were added dropwise to a 500 mL reactor and stirred. During the process, 20 mL of 0.20 g of octadecyltrimethylammonium chloride solution was added dropwise, and an appropriate amount of phosphoric acid was added to control the pH of the solution to 2.3. The reactor was sent to a heating box and heated at 585° C. for 6 h under Ar. The reactor was allowed to stand overnight, filtered, washed, and dried to obtain 11.7 g of spherical iron phosphate;

[0114] (2) 2.5 g of nanocarbon spheres, 0.06 g of manganese sulfate, 0.06 g of zinc chloride, 0.04 g of gallium sulfate, 1.5 g of methacryloyl, and 9 mL of deionized water were uniformly mixed, stirred, centrifuged, and filtered, and then dried in a drying oven at 150° C. for 5 h to obtain 3.5 g of manganese-zinc-gallium composite-loaded microcarbon sphere conductor precursor;

[0115] (3) 3.3 g of manganese zinc gallium composite supported micro carbon sphere conductor precursor, 0.5 g of 1,6-bis(dimethylamino)hexane, and 7 mL of ethanol were uniformly mixed, sent to a heating box filled with Ar, and treated at 420° C. for 35 min to obtain 3.7 g of micro carbon sphere conductor;

[0116] (4) 11.7 g of spherical iron phosphate, 0.1 g of micro-carbon sphere conductor, 1.8 g of lithium hydroxide, 0.3 g of corn syrup, and 20 mL of polyethylene glycol in step (1) were mixed and stirred, and then sent to a heating box for drying, and heated at 650° C. for 8 h under Ar to obtain 12.3 g of micro-carbon sphere conductor-doped spherical lithium iron phosphate LiFePO4@Mn-Zn / Ga.

[0117] Comparative Example 3

[0118] The lithium iron phosphate in this comparative example has a general chemical formula of LiFePO4.

[0119] The preparation method of lithium iron phosphate in this comparative example has the following specific steps:

[0120] (1) 100 mL of 0.74 mol / L ammonium dihydrogen phosphate and 73 mL of 0.50 mol / L ferric sulfate were added dropwise to a 500 mL reactor and stirred. During the process, 20 mL of 0.20 g of octadecyltrimethylammonium chloride solution was added dropwise, and an appropriate amount of phosphoric acid was added to control the pH of the solution to 2.3. The reactor was sent to a heating box and heated at 585° C. for 6 h under Ar. The reactor was allowed to stand overnight, filtered, washed, and dried to obtain 11.7 g of spherical ferric phosphate;

[0121] (2) 11.7 g of spherical iron phosphate, 1.8 g of lithium hydroxide, 0.5 g of corn syrup, and 20 mL of polyethylene glycol were mixed and stirred, and then placed in a heating box for drying and heated at 650° C. for 8 h under Ar to obtain 12.3 g of lithium iron phosphate.

[0122] Analysis of Examples 1-6 and Comparative Examples 1-3:

[0123] The spherical lithium iron phosphate positive electrode material, carbon black conductive agent, and PVDF in Example 1-6 and Comparative Example 1-3 were prepared into a slurry in a mass ratio of 80:15:5, and then coated on copper foil to prepare a pole piece, which was placed in an oven and dried at 80°C. The sodium flakes were used as the counter electrode. The electrolyte was 1.5 mol / L sodium hexafluorophosphate in propylene carbonate, Celgard2400 was used as the diaphragm, and the battery was assembled in a vacuum glove box under an argon atmosphere. The cycle performance was tested using an electrochemical workstation, and the current density of the test was 15 mAh g -1 , the charge and discharge range is 2.5~4.2V, 1-50 cycles.

[0124] Table 1 Discharge specific capacity of positive electrode materials prepared in Examples and Comparative Examples

[0125]

[0126] Table 2 Specific surface area, conductivity, D of positive electrode materials prepared in Examples and Comparative Examples 50

[0127] Group <![CDATA[BET(m 2 / g)]]> EC(S / cm) <![CDATA[D 50 (μm)]]> Example 1 20.6 0.327 0.135 Example 2 21.4 0.316 0.137 Example 3 22.6 0.332 0.135 Example 4 21.3 0.326 0.141 Example 5 21.7 0.338 0.128 Example 6 21.8 0.314 0.133 Comparative Example 1 17.6 0.278 0.148 Comparative Example 2 16.0 0.269 0.146 Comparative Example 3 14.9 0.247 0.138

[0128] Combined with Table 1-2 and Figure 4, the first discharge capacity of Example 1-6 reaches 164-166mAh / g, and the first discharge capacity of Comparative Example 1-3 is 158-159mAh / g. When the number of cycles reaches 50 times, the discharge capacity of Example 1-6 reaches 157-161mAh / g, and the first discharge capacity of Comparative Example 1-3 is 142-143mAh / g. Example 1-6 shows excellent rate and cycle performance. The specific surface area and conductivity of the spherical lithium iron phosphate prepared in Example 1-6 are higher than those of the spherical lithium iron phosphate prepared in Comparative Example 1-3, especially the specific surface area and conductivity of the spherical lithium iron phosphate prepared in Comparative Example 1 and 2 are higher than those of the spherical lithium iron phosphate prepared in Comparative Example 1-3, indicating that the structure of the spherical lithium iron phosphate treated with the composite loaded micro-carbon sphere conductor and the liquid phase ligand coating is better.

[0129] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A ligand-coated doped lithium iron phosphate, characterized in that: The general formula of the ligand-coated doped lithium iron phosphate is LiFePO4@Mn-TC / N, wherein T is at least one of zinc, nickel, copper, iron, cobalt, zirconium, aluminum, gallium, and chromium; The method for preparing the ligand-coated doped lithium iron phosphate comprises the following steps: The phosphate fertilizer, the iron source and the regulator are mixed, heated for reaction, solid-liquid separation, and the solid phase is taken for the first calcination to obtain iron phosphate; The iron phosphate, lithium source, carbon source and micro-carbon sphere conductor are mixed and stirred, and calcined for a second time to obtain micro-carbon sphere conductor doped lithium iron phosphate; The micro-carbon ball conductor is doped with lithium iron phosphate, sulfite, and liquid ligand, mixed and stirred, aged, cross-linked, and calcined for the third time to obtain the ligand-coated doped lithium iron phosphate; the micro-carbon ball conductor includes nano-carbon balls, 1,6-bis(dimethylamino)hexane, a manganese source, a T source, methacrylamide, and a dispersant; the T source includes at least one of soluble chlorides, nitrates, and sulfates of zinc, nickel, copper, iron, cobalt, zirconium, aluminum, gallium, and chromium.

2. The ligand-coated doped lithium iron phosphate according to claim 1, characterized in that: The T is at least one of zinc, nickel, copper, cobalt, zirconium and gallium.

3. The ligand-coated doped lithium iron phosphate according to claim 1, characterized in that: The Mn-TC / N is Mn-T loaded on C / N.

4. The ligand-coated doped lithium iron phosphate according to claim 1, characterized in that: The ligand-coated doped lithium iron phosphate is one of LiFePO4@Mn-Zn / Ga-C / N, LiFePO4@Mn-Cu / Co / Zr-C / N, LiFePO4@Mn-Zn / Co-C / N, LiFePO4@Mn-Co / Cu-C / N, LiFePO4@Mn-Zr / Cu-C / N, LiFePO4@Mn-Zr / Cu-C / N, LiFePO4@Mn-Zr / Cu / Co-C / N, and LiFePO4@Mn-Zn / Cu / Co-C / N.

5. The method for preparing the ligand-coated doped lithium iron phosphate according to any one of claims 1 to 4, characterized in that: The preparation method is used to prepare the ligand-coated doped lithium iron phosphate.

6. The preparation method according to claim 5, characterized in that: The following steps are involved: The phosphate fertilizer, the iron source and the regulator are mixed, heated for reaction, solid-liquid separation, and the solid phase is taken for the first calcination to obtain iron phosphate; The iron phosphate, lithium source, carbon source and micro-carbon sphere conductor are mixed and stirred, and calcined for a second time to obtain micro-carbon sphere conductor doped lithium iron phosphate; The micro-carbon ball conductor is doped with lithium iron phosphate, sulfite, and liquid ligand, mixed and stirred, aged, cross-linked, and calcined for the third time to obtain the ligand-coated doped lithium iron phosphate; the micro-carbon ball conductor includes nano-carbon balls, 1,6-bis(dimethylamino)hexane, a manganese source, a T source, methacrylamide, and a dispersant; the T source includes at least one of soluble chlorides, nitrates, and sulfates of zinc, nickel, copper, iron, cobalt, zirconium, aluminum, gallium, and chromium.

7. The preparation method according to claim 6, characterized in that: The phosphate fertilizer is at least one of diammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate or potassium phosphite; the iron source is at least one of ferric chloride, ferric acetate, ferric nitrate, ferric sulfate, ferric hydroxide or ferric oxalate.

8. The preparation method according to claim 6, characterized in that: The regulating agent is at least one of octadecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide or dodecyltrimethylammonium bromide; and the carbon source is at least one of maltose powder, corn syrup, honey, glucose powder or starch.

9. The preparation method according to claim 6, characterized in that: The liquid phase ligand is prepared by mixing a ligand and a dispersant at a solid-liquid ratio of (0.1-0.5): (2-10) g / ml; the ligand is at least one of 1,6-bis(1H-imidazole-4-carboxylic acid acyl)hexyl, 1,2-bis(1H-imidazole-4-carboxamide)ethyl, 4-hydroxy-(1,1'-biphenyl)-3,5-dicarboxylic acid dimethyl ester, and 1,1',1''-(tri(benzene-4,1-diacyl))triethyl ketone.

10. A battery, characterized in that: The invention relates to a ligand-coated doped lithium iron phosphate as claimed in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Modified lithium iron phosphate material, preparation method and application thereof

    CN108199041A

  • Positive pole material of lithium ion battery, preparation method of positive pole material and lithium ion battery

    CN109524658A

  • Carbon-coated lithium iron phosphate composite material, preparation method thereof and lithium ion battery

    CN111430687A

  • Composite material and preparation method thereof

    CN111613786A

Cited By

  • Doped lithium iron phosphate encapsulated in ligand, and preparation method therefor and use thereof

    US12531242B2